Per l'edizione dell’«Yvain en prose»: notazioni ecdotiche intorno all'episodio del "servaggio" trasmesso dal ms. NLW 444D (Carte Romanze, 2019)
The purpose of the present study is, first of all, to demonstrate the belonging of the last episode of Yvain en prose compilation – relating to the so-called Servage – to the family f of Tristan en prose. Subsequently, the stemmatic relationships that will emerge will allow to reflect on the editorial treatment to be reserved to the compilation, composed for the rest of episodes with single attestation.